كيف يُصنَعُ المواطن المنتمي والحامي للوطن؟: مسالكُ التنميَّة المركَّبة وذُلُلُ السُّنَّة النبويَّة = How to make a dedicated citizen who is willing to protected his nation?: solid structure development paths and the ways of the Prophetic Sunnah - Nasser, Youcef (Al Wasl University , Dubai, United Arab Emirates., 2019)
يقف هذا البحث على فرضية التنمية المركَّبة التي لا نراها تحصل إلا بتركيب ثلاثة عناصر، هي: السلطة والعامة والنخبة (=س، ع، ن)؛ حيث يكون الإنسان المواطن كالبنيان المرصوص يشدُّ بعضه بعضًا، ويقف سدًّا منيعًا أمام الاختراق والاحتراق. نحاجج، أيضًا، بأن التنمية المركَّبة التي من داخلها يُصنَع المواطن المنتمي والحامي للوطن، تعد حلاًّ واقعيًا في مسائل تتعلَّق بحماية الأوطان من الفتن والإحن، والتي يصعب مواجهتها إلا بمواطن مركَّب؛ حيث نلفي في السُّنَّة النبويَّة، أقوالاً وأفعالاً، ما يعزِّز هذا الترصيص بوصفه حلاًّ أثبت نجاعته في مجتمع يثرب مثلاً، الذي كان مفكَّكًا ومخترَقًا وممزَّقًا، ولما تركَّب إنسانه تمكَّن من مواجهة التحدِّيات وتلافي الضربات وحمايته من كل الجهات لسد الثغرات؛ حتى بات مجتمع يثرب مركزًا عالميًا في التنمية الروحية والمادية، ومضرب الأمثال للوطن المتماسك، والمواطن الماسك بزمام أموره الداخلية والخارجية. This study is based on the hypothesis of solid structure development that would not take place except with the combination of three elements: authority, the public and the elite (a, p and e); whereas the population are like the bricks of a tough building that strengthen on another and function as impenetrable shield and insulation from fire. We argue as well, that solid structure development through which a dedicated citizen who is willing to protect his nation is made would serve as a practical solution for problems related to protecting the nation from any discord and tribulation. Indeed, in such situations only a synthesized citizen would prevail. We found this aspect in the Prophetic Tradition that confirms further this perspective as a solution that had proven its effectiveness in the society in Medina for an example. It was a failed society on the verge of its own annihilation, but when its human was synthesized it became a force in facing challenges, standing up against any blow and protecting its corners from aggression. Subsequently, it merged as center for the spiritual and material development; a shining example of a united country populated by citizens who are in control of the internal and external matters.